Finishing performance of nitrocellulose lacquer on oil palm lumber (OPL) / Ummi Fatin Ab Razak - Ab Razak, Ummi Fatin (Faculty of Applied Sciences, 2016)
Finishing is the last process of manufacturing furniture but it is important process that will determine the value of the furniture. The finishing properties of coating material (nitrocellulose lacquer) on oil palm lumber was ascertained. The effect of finishing material system with the number of the undercoat and topcoat layer was determined. There are two system finishing application which is system A (6 sealer + 3 lacquer) and system B (4 sealer + 4 lacquer).Three types of finishing testing was used to determined the properties of nitrocellulose lacquer. There are household test, scratch test and cross-hatch test. This study used American Society for Testing and Material (ASTM) for the standard testing and procedures. The result revealed that 6x3 system has good performance in household test compared to 4x4 system. But, 6x3 and 4x4 system shows no different in heat resistance and pencil hardness test. This is because of the properties of oil palm and the characteristic of nitrocellulose lacquer